Two Dimensional Perovskites/Transition Metal Dichalcogenides Heterostructures: Puzzles and Challenges. Issue 3 (29th December 2021) - Baranowski, Michal; Surrente, Alessandro; Plochocka, Paulina
Abstract: Two‐dimensional (2D) layered materials have been in the spotlight of scientists' interest for more than a decade. The inherently weak interaction between the layers in 2D crystals allows stacking different materials and building heterostructures with novel functional properties. Here, we review the most recent advances on heterostructures composed of transition metal dichalcogenides and 2D perovskites. We show that combining these materials yields a rich and unique platform for the investigation of energy and charge transfer mechanisms, as well as band alignment engineering. We summarize the current understanding of the fascinating photophysics of these heterostructures, emphasizing the open questions related to their fundamental properties. We conclude by highlighting how this platform offers an unprecedented number of tuning knobs to control their optoelectronic properties and some potentially interesting directions to explore in the near future. Abstract :